THE ROLE OF COST MANAGEMENT STRATEGIES FOR SME BUSINESS: A CONCEPTUAL FRAMEWORK - Kajal, Zahirul Alam; Sikder, Mukut; ., Ashamoni; Panhwar, Paruss (International Journal of Small and Medium Enterprises, 2021)
The main purpose of this research is to concern analytic knowledge of the role of cost management strategies for SMEs business and create financial sustainability. SME enterprises are playing a key role in creating entrepreneurship and eliminating unemployment in every country by raising capital through various means. In this case, the expected triumph will not come unless there is a proper concept on cost management. The effectiveness of Cost Management policy for perspective Planning in the finance with a point of next and accelerate growth in SMEs business. The authors have been used a conceptual model and employed secondary data, and developed hypotheses based on the significance of research objectives. The theoretical analysis carries out the standard cost management strategies with advantages and disadvantages, and financial management is providing remarkable knowledge to SME organizations and entrepreneurs as well as emphasized for creating specific strategies based on business. The article has been conducted current theoretical knowledge, and only analyzes the accomplishment of management policies on the enhancement of SMEs business field that limits the scope of the research quarry. This research contributes to the potential knowledge and delivers an applicable conceptual framework for the 21st century of the various small and medium business sectors. JEL Classification Codes: M31, B20, M39.